Managing sport : social and cultural perspectives - Hassan, David.; Lusted, Jim. (Foundations of sport management, 2013)
"Contemporary sport is shaped by wider society. Anybody working in sport today must be aware of the broader social and cultural context within which sport operates if they are to be effective as managers or professionals. This is the first book written especially for sport management students to examine the wider social and cultural environment and to fully explain the key issues and practical implications for everyday sport management. Written by a team of leading international experts on sport management and sport in society, the book explores important topics such as: - Corporate social responsibility in sport - Race - Gender and sexuality - Sport and the media - Globalisation - Politics and policy - Social class, social capital and social exclusion Each issue is examined from the perspective of the manager or practitioner in sport, and each chapter includes a range of useful features, such as case-studies and self-test questions, to encourage the reader to think critically about the role of sport in society and about their own professional practice. This is the first sports management textbook to be based on the assumption that a more socially aware manager is a more effective manager and it should be essential reading for all sport management students"--